Style Design of Pet Dog Knitted Garment Based on Kansei Engineering (Journal of Fiber Bioengineering and Informatics, 2024)
People’s psychological needs are becoming more important with society’s development and lifestylechange. Pets, as companions and family members of human beings, provide people with emotionalsupport. Under the new relationship between people and pets, pet garment has become a popularway to enhance communication and interaction between people and animals and has commercial value.However, there is a lack of research focusing on developing pet garments that meet pet dog owners’emotional needs. This paper takes the design of a pet dog knitted garment as an example. It combinesKansei Engineering (KE) and Analytical Hierarchy Process (AHP) to guide the design practice. Itintroduces the method of a fuzzy comprehensive evaluation to verify the matching degree between thedesigned pet dog knitted garment style and the Kansei Image of the pet dog owner. The study aims toexplore a scientific design method for pet garments to meet the emotional needs of the pet dog owner.The research results show that combining KE and AHP can effectively realise the perceptual demandand make the design decision more scientific and reasonable.
Keywords: Kansei Engineering; Analytical Hierarchy Process; Pet Gog Knitted Garment; Style Design; Fuzzy Comprehensive Evaluation